Tradução, adaptação transcultural e confiabilidade do headache screening questionnaire para a língua portuguesa do Brasil - Lopes, Erika Plonczynski (2020)
Headaches are among the most prevalent diseases in the population. However, specific diagnosis and treatment are still challenging for the public health system. The Headache Screening Questionnaire (HSQ) was developed and validated in the Netherlands for clinical use, to provide health professionals with a tool capable of screening the two most common primary headache types: migraine and tension-type headache. This tool is currently available in Dutch and English. Given this scenario, the objective of this dissertation is to start the process that enables the use of the HSQ by the Brazilian population, based on the translation and cross-cultural adaptation of HSQ into Brazilian Portuguese and the reliability study of the produced version. Translation and cross-cultural adaptation followed the process of translation, synthesis, back-translation, committee of experts and pre-test. The translation phase included two independent translators, whose first language was Brazilian Portuguese and were fluent in Dutch. The back-translation had two Dutch, with Dutch mother language and fluent in Brazilian Portuguese. To verify the understanding that the Brazilian population had of the questionnaire, 60 subjects (73.3% women) with headache and over 18 years old answered the questionnaire and were interviewed (pre-test). The test re-test reliability was assessed through the Kappa analysis of the answers and results of 84 subjects (63.1% women), who fulfilled the questionnaires in two different days, with a minimum of 7 days between them. The results of the pre-test showed that all items had more than 90% of understanding by the subjects. The reliability study showed Kappa values between 0.59 and 0.9 for items in the Brazilian version of HSQ, with results of 0.80 for tension-type headache diagnoses and 0.88 for migraine. The HSQ has been translated and cross-culturally adapted in a satisfactory manner and has reproducibility at higher than moderate levels. Future studies should investigate the validity of the version produced.